2020
DOI: 10.1002/maco.202011778
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of copper in high chloride concentrations, in the context of corrosion of copper canisters

Abstract: Canisters with a cast iron insert for mechanical strength and a 50‐mm thick copper shell as corrosion protection are planned to be used for disposal of spent nuclear fuel in Sweden and Finland. Chloride can be considered “beneficial”, as it promotes active dissolution of copper rather than passivation (which might result in pitting), but a high concentration of chloride in solution would increase the driving force for corrosion through the formation of soluble copper chloro complexes. Thermodynamic calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…10b). These features can be identified as soluble CuCl 2 [52], which may enhance Cu corrosion in the solution containing chloride ions [53,54]. The surface of Cu <001> is uniformly covered with an oxide layer, which forms a compact film on the examined surface of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…10b). These features can be identified as soluble CuCl 2 [52], which may enhance Cu corrosion in the solution containing chloride ions [53,54]. The surface of Cu <001> is uniformly covered with an oxide layer, which forms a compact film on the examined surface of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of such processes are (i) the release of sulphide from the anaerobic dissolution of pyrite in the buffer, on account of the extremely low solubility of pyrite, [ 27 ] (ii) microbial activity in the deposition hole (for intact buffer), based on the argument that the minimum buffer dry density of 1400 kg/m 3 is sufficient to suppress microbial activity, [ 5 ] and (iii) uniform corrosion in O 2 ‐free H 2 O [ 3 ] or in anoxic saline solutions. [ 28 ]…”
Section: Canister Corrosionmentioning
confidence: 99%
“…In addition, Posiva‐funded work has shown that the extent of corrosion of copper in anoxic chloride solutions is insignificant for chloride concentrations less than 5 mol/kg. [ 30 ]…”
Section: Canister Evolutionmentioning
confidence: 99%